2020
DOI: 10.1182/bloodadvances.2019000784
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade for diffuse large B-cell lymphoma after autologous stem cell transplantation

Abstract: Disease relapse remains the leading cause of failure after autologous stem cell transplantation (ASCT) for patients with relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). We conducted a phase 2, multicenter, single-arm study of the anti–PD-1 monoclonal antibody pembrolizumab given after ASCT in patients with chemosensitive DLBCL, hypothesizing that it would improve the progression-free survival (PFS) at 18 months after ASCT (primary endpoint) from 60% to 80%. Pembrolizumab was administered at 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…Frigault et al evaluated the use of the anti–PD‐1 monoclonal antibody pembrolizumab after ASCT in patients with chemosensitive DLBCL in a phase 2, multicenter, single‐arm study 57 . Of a total of 29 patients treated, only 62% completed all eight planned cycles of pembrolizumab, and 79% experienced grade 3 or higher adverse event and 34% grade 2 or higher immune‐related adverse event.…”
Section: Relapsed Refractory Diseasementioning
confidence: 99%
“…Frigault et al evaluated the use of the anti–PD‐1 monoclonal antibody pembrolizumab after ASCT in patients with chemosensitive DLBCL in a phase 2, multicenter, single‐arm study 57 . Of a total of 29 patients treated, only 62% completed all eight planned cycles of pembrolizumab, and 79% experienced grade 3 or higher adverse event and 34% grade 2 or higher immune‐related adverse event.…”
Section: Relapsed Refractory Diseasementioning
confidence: 99%
“…Also, PD-1 blockade after ASCT was believed to leverage immune landscapes to decrease minimal residual disease. However, data from a phase 2 study showed that pembrolizumab consolidation given after ASCT did not improve the 18-month PFS rate (59%) [ 49 ]. Just as rituximab does not provide clinical benefits when used as post-ASCT maintenance, checkpoint inhibitors face the same challenge.…”
Section: Immunotherapymentioning
confidence: 99%
“…Most DLBCL patients were initially thought to be not amenable to PD-1 blockade since PDL-1/2 alterations are nonfrequent in this disease, and, accordingly, PD-1 blockade therapy has been disappointing to date in R/R DLBCL and FL. While several ongoing clinical trials are evaluating the use of pembrolizumab in different DLBCL subtypes, this antibody failed to improve PFS in ASCT-relapsed patients [ 102 ]. Similarly, a first phase-1b dose-escalation cohort expansion study evaluating nivolumab in R/R DLBCL patients (NCT01592370) and a subsequent larger phase-2 study (NCT02038933) in ASCT-relapsed and ASCT-ineligible DLBCL patients reported overall response rates (ORRs) <40% [ 78 , 97 , 100 , 103 ] ( Table 1 ).…”
Section: Immune Checkpoint Blockade In B-cell Lymphomamentioning
confidence: 99%